2022
DOI: 10.1186/s12936-022-04244-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards malaria diagnostics among healthcare providers and healthcare-seekers in Kondoa district, Tanzania: a multi-methodological situation analysis

Abstract: Background Despite the large-scale rollout of malaria rapid diagnostic tests (RDTs) in Tanzania, many healthcare providers (HCPs) continue using blood film microscopy (BFM) and clinical examination to diagnose malaria, which can increase the risk of mal-diagnosis and over-prescribing of anti-malarials. Patients disregarding negative test results and self-treating exacerbate the problem. This study explored the knowledge, attitudes and practices of HCPs and healthcare-seekers regarding RDTs in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Presumptive treatment of malaria in pregnant women with clinical symptoms emerged as a common practice. This has previously been documented in Kenya and other countries [30][31][32][33][34]. Women's hesitancy to be tested with a malaria RDT due to association with HIV testing has not been described previously, though women's concerns about fears of HIV testing hampering intermittent preventive treatment (IPTp) uptake in antenatal clinics have been documented [35].…”
Section: Discussionmentioning
confidence: 95%
“…Presumptive treatment of malaria in pregnant women with clinical symptoms emerged as a common practice. This has previously been documented in Kenya and other countries [30][31][32][33][34]. Women's hesitancy to be tested with a malaria RDT due to association with HIV testing has not been described previously, though women's concerns about fears of HIV testing hampering intermittent preventive treatment (IPTp) uptake in antenatal clinics have been documented [35].…”
Section: Discussionmentioning
confidence: 95%
“…However, limited access to high-quality, well-maintained microscopes and trained users restricts the accessibility of these tests. A survey of Tanzanian health clinics reported that only 42% had access to a light microscope for malaria diagnosis, dropping to just 20% of public health facilities [8]. Furthermore, there is a workforce shortage across pathology services worldwide [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, limited access to high-quality, well-maintained microscopes and trained users restricts the accessibility of these tests. A survey of Tanzanian health clinics reported that only 42% had access to a light microscope for malaria diagnosis, dropping to just 20% of public health facilities [8]. Furthermore, there is a worldwide workforce shortage across pathology services [9].…”
Section: Introductionmentioning
confidence: 99%